Synthesis of Indole and Benzimidazole Substituted Novel 16-Arylidene Steroid Derivatives - Karatas, Semra; Capan, Irfan; Servi, Suleyman (Bentham Science Publ Ltd, 2019)
Novel aza-heterocyclic substituted dehydroepiandrosterone derivatives were synthesized through a three-step reaction sequence. Some new O-alkylated 4-hydroxybenzaldehydes were synthesized from the reaction of substituted benzaldehydes with dihalogen compounds which have different chain lengths. 16-Arylidene steroids were synthesized from the base-catalyzed aldol condensation of O-alkylated 4-hydroxybenzaldehydes and dehydroepiandrosterone. New indolyl and benzimidazolyl substituted steroid derivatives as hybrid molecules were obtained from the reaction of 16-arylidene steroids with indole or benzimidazole.
Keywords: Dehydroepiandrosterone; indole; benzimidazole; 16-arylidene steroids; O-alkylated 4-hydroxybenzaldehydes; Aldol condensation